Celebrity Everyday Maker: Public Policy and the Discourse of Celebrity Surrounding Kim Kardiashian. (4th May 2021) - Jensen, Courtney
Abstract : The rise in mass media and transition to networked governance, coupled with a shift to 'policy-politics', has left the lines separating politics and celebrity culture blurred and indistinguishable. Using Kim Kardashian's efforts to establish criminal justice reform this research explores what is the celebrity role in policy making and how are these policymaking efforts portrayed using an analysis of the media discourse. This research finds that the media discourse is focused on the celebrity, particularly their importance, shifting focus away from the policy and the affect communities. In terms of her role in the policy process, this research finds that Kim Kardashian is approaching policy making less like a policy entrepreneur or activist but more like an everyday maker. For public administration this raises important questions about celebrities ability to bring awareness to an issue and how to engage everyday makers in the policy making process.